Evaluating baseline indicators pertaining to Oxfam America's Water Program in Ethiopia: a revised report prepared for Oxfam America - Mapedza, Everisto D.; Wichelns, Dennis (International Water Management Institute, 2010)
The goal of Oxfam America's Water Program in Ethiopia is to improve smallholders? food security and strengthen their livelihoods in moisture-stressed areas of Oromiya, Tigray and Amhara National Regional States. To realize this goal, smallholder households must exercise their rights to access and manage water resources sustainably and equitably, for irrigating crops and raising livestock. Better access, equitable sharing, and sustainable management are essential outcomes that must be achieved along the path to greater food security and more resilient livelihoods.